Taxonomic Revision of Fern (Pteris L.) in Peninsular Malaysia - Shahari, Rozilawati (2008)
A taxonomic revision of Pteris in Peninsular Malaysia was carried out from January 2006 to July 2007. Fifteen species of Pteris has been examined. This study was conducted to document all available taxa of Pteris, to investigate possible wrongly named or unnamed species of Pteris, and develop a dichotomous key from morphological, anatomical and spore ultrastructure characteristics. Materials for this study were obtained from both the field and herbarium collection. Pteris specimens deposited in Universiti Putra Malaysia (UPM), Universiti Kebangsaan Malaysia (UKMB), Universiti Malaya (KLU), Forest Research Institute Malaysia (KEP), and Singapore Herbarium (SING) were identified and annotated for the morphological studies. Fern specimens were also collected from several states in Peninsular Malaysia such including N.Sembilan, Perak, and Johor for the anatomical studies using light microscope to observe the shape of vascular bundle. Spore of Pteris was examined using scanning electron microscope to obtain the surface ornamentation. From this study, P. multifida Poir. was recorded as new record to Peninsular Malaysia, and two species were reported as rare and the rest of the species were common in Peninsular Malaysia. Pteris grows terrestrially in more or less shaded locations, open places and on all type of soils. Pteris also grow on old buildings such as P. vittata and in rock-crevices such as P. multifida. Morphological studies including frond architectures and study of anatomy stipe were conducted, as they are taxonomically significant for deliminating species within Pteris. Four types of frond architectures were observed. There are simple pinnate, bipinnate, bipinnatifid and tripinatifid. Mainly two types of venation were encountered within the genus Pteris in Peninsular Malaysia. The two types of veins are free veins and simple anastomosing. The stipe anatomy reveals that Pteris has hipposcampus-shaped bundle in the stele. Sori of Pteris produced at the back side of the lamina and elongated along the margins of the pinnae, but not quite reaching the base of apex and covering by false indusium. The shape of the spores of the Pteris was recognized as the triangular type which could be seen both in the light microscope and scanning electron microscope. The spores of the genus Pteris can be segregated into five different groups based on the variations in the surface structure of the spore. The surface structure of the spore of the Pteris was baculate, costate, verrucate, rugulate, and tuberculate.